Legal Aspects Occupational Safety and Health of the Work Force in the Bussiness Of Dinamis Abadi City Of Palu - Andi Reza Alief Chairin Noor; Mohamad Andri; Ahmad Yani; Sudirman Sudirman (Promotif : Jurnal Kesehatan Masyarakat, 2017)
Protection of Occupational Safety and Health given to workers is a preventive effort to prevent work accidents and occupational diseases. Occupational Safety and Health must be contained in the employment agreement, because Occupational Safety and Health is the normative right of the worker to be provided by the company. Research type using descriptive qualitative method. The results in this study are Occupational Safety and Health is important because it is closely related to the performance of employees and in turn affect the performance of the company. in fact there are companies that have not provided proper safety and health protection. In this study found the following problems: First, how the agreement is regulated in the legislation in Indonesia. Second, how the legal protection of Occupational Safety and Health according to the laws and regulations in Indonesia. Third, How to protect the law in the implementation of Occupational Safety and Health in UD. Dynamic Eternal.Keywords : Occupational Health and Safety, Health Law